Sewage sludge organic fertilizer as a promoter of initial growth of Euterpe edulis Mart., an endangered palm - Ana Carolina Cardoso de Oliveira; Ricardo Augusto Gorne Viani (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The overharvesting of the endemic palm tree Euterpe edulis Mart. (Arecaceae) from the Brazilian Atlantic Forest hotspot and the destination given to the sludge produced from urban sewage treatment are both serious environmental issues caused by human activities. In order to find solutions or alternatives for both the issues, we aimed to investigate the effect of increasing rates of a sewage sludge organic fertilizer (SSOF), produced by composting sewage sludge and solid waste, on the initial growth of E. edulis. Methods We mixed sand with 0, 62.5, 125, and 250 kg·m−3 of SSOF in 8 L (21 cm height × 24 cm top diameter × 20.5 cm base diameter) pots and then planted a seedling of E. edulis in each pot. We assessed the seedlings’ height and stem diameter relative growth rate (RGR), biomass, root to shoot ratio, and shoot macronutrient (nitrogen, phosphorous, potassium, calcium, magnesium, and sulphur) concentrations in relation to fertilizer levels. We also evaluated the relation between plant height and diameter over time for each fertilization level. Results We found that height and stem diameter RGRs, biomass accumulation, and N and P shoot concentrations of E. edulis were positively related to SSOF levels between 120 and 250 kg·m−3 in the substrate. Conclusions Our study demonstrates that SSOF can be further used as an alternative to sewage sludge disposal and contribute to E. edulis cultivation, and, hence, its conservation.